Analisis Faktor-Faktor yang Mempengaruhi Perusahaan Delisting dari Bursa Efek Indonesia Tahun 2019-2023 - Luti Junillah, Andi; Anwar, Azwar; Syachbrani, Warka (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
The purpose of this study is to analyze the effect of Current Ratio on delisting from the Indonesia Stock Exchange, (2) to analyze the effect of Debt to Asset Ratio on delisting from the Indonesia Stock Exchange, (3) to analyze the effect of Current Ratio and Debt to Asset Ratio on delisting from the Indonesia Stock Exchange. The sample of this study was six companies that experienced delisting. The data was analyzed using Logistic Regression Analysis. The results of this study indicate that, partially, the current ratio does not have a significant effect on delisting, and the debt to asset ratio does not have a significant effect on delisting. Based on the results of the determination coefficient test (Nagelkerke's R Square), the current ratio and debt to asset ratio have an effect on delisting.